State-Building, War and Violence: Evidence from Latin America - Sabine Kurtenbach (German Institute of Global and Area Studies (GIGA), 2011)
In European history, war has played a major role in state-building and the state monopoly on violence. But war is a very specific form of organized political violence, and it is decreasing on a global scale. Other patterns of armed violence now dominate, ones that seem to undermine state-building, thus preventing the replication of European experiences. As a consequence, the main focus of the current state-building debate is on fragility and a lack of violence control inside these states. Evidence from Latin American history shows that the specific patterns of the termination of both war and violence are more important than the specific patterns of their organization. Hence these patterns can be conceptualized as a critical juncture for state-building. While military victories in war, the subordination of competing armed actors and the prosecution of perpetrators are conducive for state-building, negotiated settlements, coexistence, and impunity produce instability due to competing patterns of authority, legitimacy, and social cohesion.
Keywords: 300; state-building; war; violence; critical juncture; Latin America; Krieg; Staatsgewalt; Souveränität; Lateinamerika